INTEGRASI TEKNOLOGI WEARABLE DALAM PEMANTAUAN KESEHATAN JANTUNG PADA WANITA PASCAMENOPAUSE STUDI KASUS DI PAGUYUBAN LANSIA BAHAGIA YUSWA KENCANA SEMARANG: INTEGRATION OF WEARABLE TECHNOLOGY IN HEART HEALTH MONITORING FOR POSTMENOPAUSAL ELDERLY WOMEN AT PAGUYUBAN LANSIA BAHAGIA YUSWA KENCANA IN SEMARANG - Dewi, Ratih Kumala; wahyuningsih; Pande Putu Novi Ekajayanti (Politeknik Insan Husada Surakarta, 2025)
Cardiovascular diseases are a leading cause of death among post-menopausal women, particularly in urban areas with sedentary lifestyles. This study aims to evaluate the effectiveness of using smartwatches to monitor health parameters, such as heart rate, blood pressure, and physical activity, among elderly post-menopausal women in the Paguyuban Lansia Bahagia Yuswa Kencana, Semarang. A quasi-experimental design with pre-test and post-test, without a control group, involved 32 participants selected through purposive sampling. Measurements were taken before and after using the smartwatch. Results showed significant reductions in heart rate (from 80 ± 5.2 BPM to 72 ± 4.5 BPM, P-value = 0.02), systolic blood pressure (from 135 ± 8.3 mmHg to 128 ± 7.6 mmHg, P-value = 0.04), and increased physical activity (from 4500 ± 1200 steps to 5500 ± 800 steps per day, P-value = 0.01). Acceptance of the technology was positive, with 62.5% of participants reporting ease of use and 70% believing the device helped monitor their health. This study concludes that the use of smartwatches is effective in monitoring health and improving physical activity in post-menopausal elderly women. Key words : Smartwatch, Cardiovascular Health, Elderly Women